The Landscape of Clinical Implementation of Pharmacogenetic Testing in Central China: A Single-Center Study - Zhang J; Qi G; Han C; Zhou Y; Yang Y; Wang X; Liu S; Zhang X (Dove Medical Press, 2021)
Jingmin Zhang,1,2 Guangzhao Qi,1,2 Chao Han,1,2 Yubing Zhou,1,2 Yongjie Yang,1 Xinru Wang,1,2 Suna Liu,3 Xiaojian Zhang1,2 1Department of Pharmacy, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, People's Republic of China; 2Henan Key Laboratory for Precision Clinical Pharmacy, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, People's Republic of China; 3Newborn Screening Center, Department of Pediatrics, The Third Affiliated Hospital of Zhengzhou University, Zhengzhou, People's Republic of ChinaCorrespondence: Guangzhao Qi; Xiaojian Zhang Tel +86-37166295269Email qiguangzhao1223@sina.com; zhangxiaojian15@126.comPurpose: Pharmacogenetic testing is recognized as the major method for the individualized pharmacotherapy in clinical pharmacy practice, but information about the clinical implementation of pharmacogenetic testing in China is limited. The present study aimed to determine the situation of clinical implementation for pharmacogenetic testing in central China.Methods: The study is conducted in the department of clinical pharmacy in The First Affiliated Hospital of Zhengzhou University, Zhengzhou, China. We collected and analyzed pharmacogenetic testing results from November 1, 2013 to November 2, 2018 in our hospital, which were checked in the electronic medical record system. The main outcome measures were the number and type of pharmacogenetic testing across five years.Results: A total of 47,265 (56.9% male, mean age = 51.5 years) pharmacogenetic testing results were obtained with an average annual rate of growth of 63.0% across five years. A 50.2% (23,748/47,265) of all the pharmacogenetic testing results were for the determination of cytochrome P450 2C19 (CYP2C19) *2, *3 genotypes, and 41.7% were for the methylene tetrahydrofolate reductase (MTHFR) C677T genotype. The number of departments performing the pharmacogenetic testing was 35, 63, 55, 52, 52 and 39 for 2013- 2018, respectively, and the main top five departments were cardiology, psychiatry, ICU, cardiac surgery and intervention.Conclusion: Clinical implementation of pharmacogenetic testing in China is growing rapidly, but the types and implementing departments of pharmacogenetic testing were limited. Our present study reported the real-world implementation modality of pharmacogenomic tests in China. It will help us to understand the testing of pharmacogenetics in China in order to promote the rational development of pharmacogenetics.Keywords: clinical implementation, pharmacogenomics, pharmacogenetics, China, preemptive